Effect of TU‐100 on Peyer's patches in a bacterial translocation rat model. Issue 5 (5th April 2021) - Takasu, Chie; Miyazaki, Katsuki; Yoshikawa, Kozo; Nishi, Masaaki; Tokunaga, Takuya; Kashihara, Hideya; Yoshimoto, Toshiaki; Ogawa, Hirohisa; Morine, Yuji; Shimada, Mitsuo
Abstract: Background: Daikenchuto (TU‐100), a Japanese herbal medicine, is widely used for various gastrointestinal diseases. We have previously reported that TU‐100 suppresses CPT‐11‐induced bacterial translocation (BT) by maintaining the diversity of the microbiome. In this study we show that TU‐100 modulates the immune response during BT by inducing PD‐1 expression in Peyer's patches. Methods: Eighteen male Wistar rats were divided into four groups: a control group; a control + TU‐100 group, given TU‐100 1000 mg/kg orally for 5 d; a BT group, given CPT‐11 250 mg/kg intra‐peritoneal for 2 d; and a TU‐100 group, given TU‐100 1000 mg/kg orally for 5 d with CPT‐11 250 mg/kg intra‐peritoneal on days 4 and 5. Results: The size of Peyer's patch was significantly bigger in the BT group compared to the control group (9.0 × 104 µm 2 vs 29.4 × 104 µm 2, P < .05), but improved in the TU‐100 group (15.4 × 104 µm 2, P < .005). TU‐100 significantly induced PD‐1 expression in Peyer's patch compared to the control group and the BT group (control vs BT vs TU‐100 = 4.3 ± 4.9 vs 5.1 ± 10.3 vs 17.9 ± 17.8). The CD4 + cells were increased in the BT group ( P < .05) compared to the control group but decreased in the TU‐100 group. The Foxp3 + cells were increased in the BT group compared to the control group ( P < .05), and further increased in the TU‐100 group compared to the BT group. CPT‐11 significantly increased TLR4, NF‐κβ, TNF‐α mRNA expressions in the BT group. TU‐100 cotreatment significantly reversed these mRNA expressions. Conclusion: TU‐100 may have a protective effect against BT through PD‐1 expression in Peyer's patch. Abstract : Daikenchuto (TU‐100), a Japanese herbal medicine, is widely used for various gastrointestinal diseases. We have previously reported that TU‐100 suppresses CPT‐11‐induced bacterial translocation (BT) by maintaining the diversity of the microbiome. In this study, we show that TU‐100 modulates the immune response during BT by inducing PD‐1 expression in Peyer's patches.